1269 Levene Index at Different Gestational Ages in Infants < 32 Weeks. (October 2012) - Shim, R; Gnanasakaran, R; Boyle, M; Ryan, S; Tarrant, A; McCallion, N
Abstract : Background: Levene index is used for the diagnosis of ventricular enlargement, including intraventricular haemorrahage and post haemorragic ventricular dilation. The original data dates from the 1980s and more recent studies are based on relatively small numbers of infants. Aim: To describe normal values for Levene Index at different gestations. Method: The serial cranial ultrasounds were reviewed of all preterm infants with gestation under 32 weeks admitted to Rotunda Hospital from January 2009 to December 2011. Ultrasounds with Grade III or IV IVH or PVL were excluded. The data collected was grouped according to gestational age at the time of scan from 24 weeks to 32 weeks. Results: 634 cranial ultrasounds from 255 infants were reviewed. The median values show a general trend of increase as gestation increases. Conclusion: This study shows that there is a slight increase in Levene index as gestation at the time of scan increases.